Detecção de enzimas hidrolíticas em bactérias mesofílicas isoladas de lodo de esgoto, Estação Mangueira, Recife, Pernambuco - Albuquerque, Ubirajara Samuel de (2009)
The sewage sludge is a resultant residue of the system of residuary biological water treatment proceeding, presents in its chemical composition one high concentration of organic components and inorganic, that after treatments, can be used in agriculture, however its application to the ground modifies many times the physical parameters, chemical and biological of the ground. The ground is a complex system that a variety of microhabitats with different physical and chemical gradients understands and discontinues ambient conditions. The metal presence weighed in the sewer sludge, limits its use in the processes of fertilization of the ground, had to the high degree of toxicity through the absorption for the plants, that will feed the herbivorous, the metals can enter in the alimentary chain, arriving at the consumers first-class and the man, and the high index of pathogenicity proceeding from pathogenic microorganisms gifts. The action of microbiota present in not barren ground and the plants, is one of the main factors of removal of pathogenic microorganisms that arrive with the sewer at the ground, contaminating this environment many times of irreversible form. The process of mineralization of the organic substance is catalyzed by different enzymes, produced in its majority for microorganisms gifts in the ground. Assays of isolation, identification and enzymatic detention in mesophilic bacteria had been carried through gifts in the silt of sewer collected in the Station Hose in different temperatures (28 and 37oC) and in the presence and/or absence of NaCl. They had been detected in both tested temperatures, pathogenic bacteria (Escherichia coli, Pseudomonas sp, Alcaligenes sp). In screening enzymatic carried through, in the resulted detention of amylase the best ones had been gotten in the samples of the 28 ºC isolated mesophilic bacteria and in the resulted detention of urease the best ones had been gotten in the 37 ºC samples